Pascal short-pulse plus subthreshold endpoint management laser therapy for diabetic macular edema: the “sandwich technique” - J. A. Cardillo; M. W. Rodrigues; R. C. Oliveira; A. M. V. Messias; R. Jorge (International Journal of Retina and Vitreous, 2022)
Abstract Background Diabetic macular edema (DME) is the main cause of visual loss in diabetic patients. Despite the use of anti-VEGF therapy as first-line treatment, there are many patients whose response to treatment is poor or transient at best. Sophisticated laser techniques have emerged aiming at low-intensity retinal damage, avoiding excessive heat that causes tissue necrosis and related collateral effects. Objective To evaluate the effect of combined sublethal laser modalities from short-pulse duration (SPD) with endpoint management (EpM) subthreshold laser [named the “sandwich technique” (SWiT)] on central subfield thickness (CST) and best-corrected visual acuity (BCVA) in patients with DME. Material and methods In this consecutive retrospective study, 37 patients (37 eyes) with center-involved (CI) DME were treated with SWiT laser therapy from April 2017 to June 2021. The technique consisted of a mean number of 200 (range number 50–400) SPD laser burns OCT-guided thickened area performed on the juxta- and perifoveal area 500 µm away from the foveal center, overlapping with a mean number of 1000 (range number 800–1200) EpM laser burns focused on 6 mm macular diameter area but saving 300 µm toward the foveal center. All patients underwent ophthalmological evaluations, including BCVA and CST measurement by spectral-domain optical coherence tomography (SD-OCT), before and after SWiT laser therapy. The mean follow-up time was 19.2 months (range 2–60 months). Results Thirty-five out of 37 cases showed an improvement in CST and BCVA following treatment. At baseline, mean CST (µm) ± standard error (SE) and mean BCVA (logMAR) ± SE was 456.95 ± 37.00 and 0.71 ± 0.29, respectively. After a mean follow-up of 19.2 months, mean CST (µm) ± SE and BCVA (logMAR) ± SE were 272.09 ± 9.10 (p < 0.0001) and 0.54 ± 0.26 (p = 0.003), respectively. A statistically significant reduction in CST and improvement in BCVA was noted after laser therapy application. The anti-VEGF injection frequency was reduced during the mean 19.2 months of the study period. Conclusions The novel “sandwich” laser therapy aid reduced CST and improved BCVA in this retrospective case series. Further prospective studies are warranted.